Pengaruh Refocusing dan Realokasi Anggaran terhadap Kualitas Laporan Keuangan - Ihyani, Layali; Marlina, Febria Nurmelia; Marswandi, Ega Dwi Putri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the effect of budget refocusing and reallocation on the quality of regional financial reports. The study population is employees in the accounting department in 43 regional apparatus organizations (OPD) of the West Lombok Regency Regional Government. The sampling technique uses the purposive sampling method with a sample of 117 respondents.  The respondents consisted of financial administration officials, treasurers, and accounting staff who had the task of compiling financial statements. The data analysis method is by using regression analysis. The results of the study stated that partially, refocusing had an insignificant positive effect on the quality of financial statements. Meanwhile, budget reallocation has a significant positive influence on the quality of regional financial reports. So that these results can provide input for policymakers and stakeholders in terms of refocusing and reallocating budgets for both central and regional governments.